2021
DOI: 10.1186/s12870-021-02934-6
|View full text |Cite
|
Sign up to set email alerts
|

A source-sink model explains the difference in the metabolic mechanism of mechanical damage to young and senescing leaves in Catharanthus roseus

Abstract: Background Mechanical damage is an unavoidable threat to the growth and survival of plants. Although a wound to senescing (lower) leaves improves plant vitality, a wound to younger (upper) leaves often causes damage to or death of the whole plant. Source-sink models are often used to explain how plants respond to biotic or abiotic stresses. In this study, a source-sink model was used to explain the difference in the metabolic mechanism of mechanical damage to young and senescing leaves of Catha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Our GC-MS results showed that gallic acid, vanillic acid, protocatechuic acid, and catechol, acids subordinated to phenolic compounds, were obviously accumulated. These compounds are secondary metabolites that originate from phenylalanine metabolism [ 42 44 ]. Gallic acid and protocatechuic acid are the precursors of tannins, which can affect plant thickness and reduce water evaporation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our GC-MS results showed that gallic acid, vanillic acid, protocatechuic acid, and catechol, acids subordinated to phenolic compounds, were obviously accumulated. These compounds are secondary metabolites that originate from phenylalanine metabolism [ 42 44 ]. Gallic acid and protocatechuic acid are the precursors of tannins, which can affect plant thickness and reduce water evaporation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic compound detection was performed as previously described [ 42 ]. After treatment with liquid nitrogen, a 1.0 g pulverized sample was dissolved in 20 mL methanol for extraction and ultrasonicated at low frequency for 40 min.…”
Section: Methodsmentioning
confidence: 99%
“…Our GC-MS results showed that gallic acid, vanillic acid, protocatechuic acid, and catechol, acids subordinated to phenolic compounds, were obviously accumulated. These compounds are secondary metabolites that originate from phenylalanine metabolism [20,42,43]. Gallic acid and protocatechuic acid are the precursors of tannin, which can affect plant thickness and reduce water evaporation [19].…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic compound detection was performed as previously described [20]. After treatment with liquid nitrogen, 1.0 g pulverized sample was dissolved in 20 mL methanol for extraction and ultrasonicated at low-frequency for 40 min.…”
Section: Phenolic Compound Detectionmentioning
confidence: 99%
“…The detection of phenolic compounds was conducted as previously described ( Chen et al, 2021 ). Briefly, 1.0 g of liquid nitrogen pulverized sample was weighed and dissolved in 20 mL of methanol for extraction.…”
Section: Methodsmentioning
confidence: 99%